Alternative approaches in music education : case studies from the field - Clements, Ann Callistro; MENC, the National Association for Music Education (U.S.) (Lanham, Md. : Rowman & Littlefield Education, 2010)
"The lived experiences evident in the cases presented in Alternative Approaches in Music Education provide an extensive, significant basis for rich discussions in music teacher education. The reader will be challenged to think broadly about the meaning and purpose of music education, and ways to reach students beyond the traditional music curriculum. The editor and authors are to be commended for their work in compiling these depictions that remind us again of the importance of music for all."-Linda Thompson, immediate past-chair, Society for Music Teacher Education.
"Music education is a dynamic field, responsive to the needs of students, teachers, schools, and society. The case studies of curricular innovation in this collection provide tangible evidence of this growth. The authors give us new models and paths to analyze, consider, and adapt as we seek to open up more musical opportunites for more students to engage in the satisfactions and challenges of musical engagement. Congratulations to the authors, editor, and contributors to the Critial Examination of the Curriculum group of the Society for Music Teacher Education."-Janet R. Barrett, chair-elect of the Society for Music Teacher Education; Northwestern University.
Explore the creative ways music educators across the country are emerging practices in music teaching and learning. Outlined in twenty-five unique case studies, each program offers a new perspective on music taching and learning, often falling outside the standard music education curriculum. Find innovative ideas and models of successful practices to incorporate into your teaching, whether in school, university, or community settings.
Ann C. Clements is associate professor of music education at the Pennsylvania State University. --Book Jacket.
-- Part I: PREK - 12 case studies. Opening spaces in the instrumental music classroom / Carlos Abril ; Guitar class and the popular music ensemble / Joseph Abramo ; Toward a new conception of world music education : the virtual field experience / Sarah J. Bartolome ; Discovering world music and children's worlds : pedagogy responding to children's learning needs / Lily Chen-Hafteck ; The Lakewood project : rockin' out with informal music learning / Megan Clay Constantine ; Music tech, adaptive music, and rock band 101 : engaging middle school-age students in general music class / Mary L. Cohen and Cecilia Roudabush ; Rock 'n' roll high school : a genre comes of age in the curriculum / Robert Gardner ; Lead lines, licks, and everything in between : popular music in a preschool music classroom / Beth Gibbs and Mark Ross ; Starting young : developing a successful instrumental music program in kindergarten / Elizabeth M. Guerriero and Matthew Hoy ; Music in cyberspace : exploring new models in education / Sheri E. Jaffurs and Betty Anne Younker ; Exploring the creation of music through film scoring / Douglas C. Orzolek ; Alternatives to music education : east meets west in music education / Lisa M. Meyer, Catherine Odom Prowse, and Terese Volk Tuohey ; Steel drums in a middle school setting / Barbara J. Resch ; Talkin' turkey : incorporating music from Turkey in the elementary general music class / Christopher Roberts ; Enhancing the instrumental music program with creativity / Nancy Beitler and Linda Thornton -- Part 2: School to community and higher education case studies. O passo (The step) : a critical pedagogy for music education from Brazil / Frank Abrahams ; Cultural bearers in the children's choral ensemble / Ruth O. Boshkoff and Brent M. Gault ; A unique collaboration : the Fairview Elementary School string project / Brenda Brenner ; New wine in old skins : making music with older adults / Don D. Coffman ; Compose yourself : older people and GarageBand / Jonathan D. Harnum ; Democratic jazz : two perspectives on a collaborative improvisation jazz workshop / Victor Lin and Joshua S. Renick ; If the shoe fits : tapping into the potential of an undergraduate peer-teaching experience to promote music teacher and music teacher educator socialization and identity / Alison M. Reynolds ; Crossing borders : building bridges for an international exchange in music teacher education / Janet Robbins ; The rock project : informal learning in secondary general methods / Katherine Strand and Daniel Sumner ; Rekindling the playful spirit : learning to teach through play / Sarah H. Watts.
"Published in partnership with MENC: The National Association for Music Education."
Includes bibliographical references.
Keywords: Music -- Instruction and study -- United States; School music -- Instruction and study -- United States